Entwicklung von Steuerungskennzahlen kapitalmarktorientierter Unternehmen im Prime Standard seit der Einführung des DRS 20 - Philipp Blumenstein; Robert C. Schmidt; Jessica Hastenteufel (IU Internationale Hochschule, 2022)
– This paper examines the performance indicators of 168 prime standard entities since the introduction of German Accounting Standard (Deutscher Rechnungslegungs Standard (DRS)) No. 20, focusing on the core question of how the use of performance indicators has changed over time. For this purpose, we compare the published key performance indicators from various companies in different years to point out existing differences. Furthermore, we examine which KPIs are changed most often and how frequently businesses adjust their performance indicators. The companies examined are differentiated according to size and sector.
Keywords: G00; G34; M41; 650; DRS 20; Prime Standard; Steuerungskennzahlen; Key Performance Indicators; KPIs